1996
DOI: 10.2739/kurumemedj.43.101
|View full text |Cite
|
Sign up to set email alerts
|

A Case Report of Rectal Schwannoma.

Abstract: We experienced a case of rectal schwannoma which was diagnosed before surgery. In this paper we have described this rare case and have discussed a number of similar cases reported in the literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 5 publications
(2 reference statements)
0
3
0
Order By: Relevance
“…Stout et al reported that 2 tumors of 48 patients with the primary gastrointestinal schwannoma were found in the lower intestine [4]. In the Japanese literatures, to our knowledge, only 51 cases have been reported in Japan since 1940 [8][9][10][11][12]. The mean age of the 52 patients, including our case, was 58 years, with a range from 12 to 76 years.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Stout et al reported that 2 tumors of 48 patients with the primary gastrointestinal schwannoma were found in the lower intestine [4]. In the Japanese literatures, to our knowledge, only 51 cases have been reported in Japan since 1940 [8][9][10][11][12]. The mean age of the 52 patients, including our case, was 58 years, with a range from 12 to 76 years.…”
Section: Discussionmentioning
confidence: 87%
“…Barium enema with colonoscopy usually reveal a submucosal tumor. Only 8 cases were correctly diagnosed before operation [12,14]. Diagnosis must differentiate the schwannoma from the leiomyoma and the leiomyosarcoma.…”
Section: Discussionmentioning
confidence: 99%
“…4 Common sites for GANTs include the stomach, duodenum, jejunum, ileum 5 and to date literature search has revealed only twenty cases of colonic schwannomas and only four reported cases of rectal schwannomas. 2,[6][7][8][9] We report rare GANTs of colon.…”
Section: Introductionmentioning
confidence: 99%